Lord Edgware dies [videorecording (DVD)] - Horowitz, Anthony, 1955-; Suchet, David; Fraser, Hugh; Jackson, Philip, 1948-; Moran, Pauline; O'Dell, Chris; Gunning, Chris; Christie, Agatha, 1890-1976 (A & E Home Video, 1999)
Poirot agrees to visit the husband of a famous actress to urge him to reconsider her request for a divorce. Edgware insists that he has already agreed to his wife's request. Yet, within twenty-four hours, he is found murdered.